Astronomia cultural: formação continuada para professores e professoras dos anos iniciais - Costa, João Fabio Peixinho (2023)
This research, entitled "Cultural Astronomy: Continuing Education for Teachers of the Early Years of Primary School," promotes a continuing education course for Early Years teachers on the subject of Cultural Astronomy. The research subjects were 11 teachers of the Early Years (1st to 5th grade), from the Escola Núcleo Municipal Professora Julieta Frutuoso de Araujo, located in the city of Feira de Santana - BA, in the district of Tiquaruçu, in the rural area of the city. To format the course, a methodological path based on qualitative, ethnographic, and case study research approaches was followed. The following steps were taken: a questionnaire survey with the subjects of the research; drawing up a profile of the teachers, as well as defining the format of the course; analysis of the Geography textbook used by the teachers, focusing on the content relating to Cultural Astronomy. The analysis shows that, in addition to other aspects, most of the teachers are women who work 40 hours a week, and that the textbook used in their classes does not include the theme of Cultural Astronomy, prompting the production of a para-didactic book as complementary material to be used with students in the Early Years of Primary School. The theoretical basis of the research is established in the discussion on teacher training in Brazil, the concepts of Cultural Astronomy, intercultural education, and decolonial thinking. With elements from these theoretical perspectives, the questionnaire, and the analysis of the textbook, two educational products have been generated: a Continuing Education Course in Cultural Astronomy, using the workshop methodology, and a para-didactic as complementary material to the textbook, on the theme of Cultural Astronomy. Based on the workshops held,a tutorial was created for the production of didactic material to mediate the teaching of astronomy content: zodiacal and indigenous constellations, the apparent movement of the Sun, solstices, and equinoxes. We opted for a face-to-face workshop format and the use of a chat application (WhatsApp) for the period between the workshops. The result was a dissemination of scientific knowledge related to Cultural Astronomy with the subjects of the research, valuing intercultural teaching from a decolonial perspective, in addition to the ongoing implementation of one of the educational products developed, the paradidactic, in the 4th and 5th-grade classes.